2022
DOI: 10.37939/jrmc.v26i2.1669
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Weight on Self-Esteem among Undergraduate Young Adult Students of Doctor of Physiotherapy, Karachi

Abstract: Objectives: To determine the recurrence of body disappointment, loss of control and self- related wellbeing in interpose the relationship among body weight and impairments in self-esteem among students of Doctor of Physiotherapy (DPT) in both campuses of IPMR of DUHS, Karachi. Material and Methods: The research was among youthful understudies of the two sexes (boys and girls) of Doctor of Physiotherapy in both campuses of IPMR of Dow University of Health Sciences (DUHS), Karachi. Concluded an overview th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, this study was done on professional college students and the study claimed that this was due to the gender imbalance in the sample, with girls outnumbering boys. 18 A study by Bhadouria and Bhadoria extended on these findings and reported that self-esteem was lower among adolescent girls who fall under the obese and overweight category than normal-weight girls. 22 We compared self-esteem with BMI in the obese and overweight categories (Table 5).…”
Section: Self-esteem Score Related To Age and Gendermentioning
confidence: 93%
See 1 more Smart Citation
“…However, this study was done on professional college students and the study claimed that this was due to the gender imbalance in the sample, with girls outnumbering boys. 18 A study by Bhadouria and Bhadoria extended on these findings and reported that self-esteem was lower among adolescent girls who fall under the obese and overweight category than normal-weight girls. 22 We compared self-esteem with BMI in the obese and overweight categories (Table 5).…”
Section: Self-esteem Score Related To Age and Gendermentioning
confidence: 93%
“…Other studies have also reported the highest self-esteem in the normal weight category and the lowest in the obese category. 18 Anitha and William examined self-esteem and BMI in 60 Indian preteens where they found a significant negative correlation between BMI and self-esteem which meant that as adolescent BMI increased, self-esteem decreased. 19 On comparing BMI and gender (Table 2) in our study, we found that boys were more underweight than girls (62.57% vs 56.88%), and more overweight too (6.42% vs 3.67%) whereas, obesity was more in girls (8.26% vs 6.95%).…”
Section: Self-esteem Score Related To Age and Gendermentioning
confidence: 99%
“…Self-image is a mental picture of their own personality or the structured declarative knowledge of who they are that could influence how they behave in social situations. Self-image refers to how we evaluate our own psychological, emotional, and physical traits and the implications of our ego and social standing (Naz et al, 2019). It's crucial to have an accurate self-perception in order to understand one's own behavioral knowledge and attitude capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…It's crucial to have an accurate self-perception in order to understand one's own behavioral knowledge and attitude capabilities. Young women's incapacity to establish a physical appearance that conforms to the ideal concept of beauty leads to a negative self-image (Naz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%